The Treatment of Information Regarding Female Victims of Sexual Violence in the Media (with Special Attention to Social Media) - Mina Mendoza, Arnaldo (2026)
The research addresses the persistent sexual violence against women in the 21st century, analyzing the role of digital media in prominent cases.